Tom Wolfe's America. - McEneaney, Kevin (ABC-CLIO, 2009)
While The Right Stuff and The Bonfire of the Vanities remain perhaps his best-known works, Tom Wolfe's journalism and fiction continues to enjoy a large audience, perhaps chiefly because of the variety of his subjects and his controversial approach to them. Here, McEneaney offers an account of the man and his works, explaining along the way Wolfe's use of irony, his obsessive themes, and even his use of pranks. More comprehensive in scope than any preceding book on Wolfe, it offers accurate and accessible commentary based upon what Wolfe admits about his own work. In this new book, Wolfe'